2020
DOI: 10.1002/ijgo.13262
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to improve maternal and perinatal outcomes in rural Guatemala: A stepped‐wedge cluster randomized trial

Abstract: Objective To evaluate the impact of an intervention package on maternal and newborn health indicators. Methods A randomized stepped‐wedge non‐blind trial was conducted across six subdistricts within two districts in Guatemala from January 2014 to January 2017. Data on outcomes were collected on all deliveries in all 33 health centers. The intervention package included distribution of promotional materials encouraging health center delivery; education for traditional birth attendants about the importance of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The absence of information on mortality associated with PAS in the English-language literature is remarkable. There are a few publications in Japanese 3 and in the LMIC population 19,20 describing details about fatal cases. In this study, failures in the diagnosis process were detected in 64.6% of cases, including the inability to detect PAS by prenatal ultrasound in 63.9% of the cases (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The absence of information on mortality associated with PAS in the English-language literature is remarkable. There are a few publications in Japanese 3 and in the LMIC population 19,20 describing details about fatal cases. In this study, failures in the diagnosis process were detected in 64.6% of cases, including the inability to detect PAS by prenatal ultrasound in 63.9% of the cases (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Unique components of the PTBi intervention like simulation and team training implemented in Mexico demonstrated that it can reduce neonatal mortality [14]. In other studies, from Guatemala and India, PRONTO's simulation and team training increased use of evidence-based practices in normal and complicated deliveries when these activities were integrated along with didactic teaching and demonstrations [15][16][17][18]. Similar packaged interventions are currently being implemented in several sub-Saharan countries to examine if individual components can synergistically act with each other to bring about a larger reduction in perinatal mortality [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…PRONTO International is a non-governmental organization whose simulation and team-training curriculum has been implemented in a variety of clinical settings, from primary health centers to district and regional hospitals (24)(25)(26)(27). The PRONTO model has been applied and evaluated in multiple settings, including East Africa, and has been shown to improve provider skills (25,27,28), reduce morbidity and mortality(26, [29][30][31], and improve the use of RMC practices (9). The interactive curriculum is based on simulation and debrie ng of clinical scenarios, case-based learning, skills stations, and teamwork activities.…”
Section: Intervention Conditionmentioning
confidence: 99%